Getting Down to Earth (and Business): Focus on African Smallholders' Incentives for Improved Soil Management - Klauser, Dominik; Negra, Christine (Frontiers in Sustainable Food Systems, 2020)
Soil degradation poses a major challenge to agricultural systems in sub-Saharan Africa. Whereas there is a wealth of knowledge on the consequences of degraded soils as well as on agronomic practices that could prevent and mitigate soil degradation processes, farmer uptake of such practices remains mostly low. We propose that this is – amongst other factors – a consequence of the lack of incentive systems that provide immediate financial benefits for farmers to adopt sustainable management practices associated with enhanced soil health. With this paper, we aim to review and evaluate potentially monetizable agronomic and environmental benefits of such practices, at the farm level, in order to better understand existing bottlenecks and develop guidelines for initiatives that facilitate the scaled-up adoption of sustainable production practices To encourage soil health initiatives that are simultaneously evidence-driven and ROI-focused, we propose that initiatives seeking to enhance the uptake of sustainable production practices by African smallholder farmers will benefit from a design based on a thorough analysis of both anticipated benefits and beneficiaries of the promoted interventions. This should be built on a solid evidence base and robust data, acquired over several consecutive seasons and considering local specificities. Furthermore, such interventions will benefit from clear business models that provide farmers immediate monetary incentives to adopt more sustainable production practices and inputs.